GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG POLA MAKAN BALITA DI POSYANDU DUSUN GENTAN KECAMATAN KALIKAJAR KABUPATEN WONOSOBO - Nur Sholichah; Intan Permata Sari (Jurnal Komunikasi Kesehatan, 2021)
Based on a preliminary study conducted by interviewing 10 mothers of children under five in the village of Gentan. They were asked about what diet is, the impact of an unhealthy diet, the principles of eating patterns and the benefits of eating patterns. The purpose of this study was to describe the level of knowledge of mothers about the eating patterns of toddlers in Gentan Village based on the characteristics of the respondents. Research Methods: This research method is descriptive with a cross sectional approach. The population in this study was 53 respondents, the sample was taken using purposive sampling technique. The sample in this study was 48 respondents. The measuring instrument uses a questionnaire. Data analysis using univariate. The results of the study were 35.8% (19 respondents) with good knowledge, 62.3% (33 respondents) knowledgeable and 1.9% less knowledgeable (1 respondent). Based on the results of the study, it was concluded that the level of knowledge of the mother's level of knowledge about the eating patterns of toddlers in the village of Gentan was well informed. It is hoped that the mother of toddlers will add insight into information and education about toddlers' eating patterns.